The Effect of Magnetic Maze Media on Problem-Solving and Fine Motor Skills in 5-6 Year Old Children at TK Islam Al-Abrar Makassar - Arianti, Sri Dewi; Musi, Muhammad Akil; Saodi, Syamsuardi -; Lismayani, Angri - (PIAUD Universitas Islam Negeri Sunan Kudus, 2024)
Problem-solving and fine motor skills are critical for young children, as they mutually reinforce each other’s development. Incorporating engaging and educational media tools in early childhood learning is essential to ensure effective and enjoyable activities. This study investigates the impact of magnetic maze media on the problem-solving and fine motor skills of children aged 5–6 years at Al-Abrar Islamic Kindergarten. The research employed a quasi-experimental design with a non-equivalent group approach. It used a purposive sampling technique to select 21 children from a population of 42 children as the experimental group. Data were analyzed using descriptive statistics and parametric tests, including normality and hypothesis testing. The findings indicate that magnetic maze media significantly enhances problem-solving and fine motor skills in children aged 5–6. This conclusion is supported by a paired-sample t-test, which revealed significant differences between children who engaged with the magnetic maze and those who did not. This study highlights the effectiveness of magnetic maze media as a learning tool for improving cognitive skills, particularly problem-solving and fine motor skills, in young children.